Inclusive Economy Acceleration: Optimize The Existence and Export Opportunity of Village Based Superior Product - Dian Rizqi Khusnul Khotimah (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
The government has made area-based sustainable development strategy as the main focus through the Village SDGs. This study aims to analyze village based superior product in East Java Province using the Potential Village 2021 microdata from Statistics Indonesia. The analytical methods used are linear regression and multinomial logistic regression using the Synthetic Minority Oversampling Technique. This study found that the proportion of villages with superior product had a significant impact on inclusive economic development between districts/cities in East Java Province. Various socio-economic features of the village show significant effect that can be used to optimize the existence and export opportunities of superior product. Village based superior products can become a new regional-based economic resource for accelerating inclusive economic development in East Java Province.